The Effectiveness Of Hypnobirthing In Reducing Low Back Pain Among Pregnant Women: A Literature Review - Murbiah, Murbiah; Panduragan, Santhna Letchmi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Introduction: Pregnancy is the physiological state in which a woman undergoes the development and growth of a fetus within her uterus. The increase in gestational age leads to a more significant number of changes experienced by pregnant mothers, such as discomfort in the lower back, particularly towards the end of pregnancy. One way to alleviate lower back pain is through the practice of hypnobirthing. Material and Methods: This study is a literature review examining the efficacy of hypnobirthing in alleviating low back pain in pregnant women. Articles about the specific theme were chosen from 2018 to 2023 using electronic databases, including Science Direct, PubMed, and Google Scholar, as well as open knowledge maps throughout the article search. The analysis of literature studies was conducted using the PRISMA approach by researchers. Results: Of the total 138 articles selected, 13 studies were eligible and thoroughly reviewed, and only 10 could be analyzed. In the results of this study, no one conducted research on the Effectiveness of Hypnobirthing in Reducing Low Back Pain Among Pregnant Women. Researchers found research on hypnobirthing but with different objectives or samples. Similarly, to overcome low back pain in pregnant women, researchers did not find hypnobirthing as an intervention. Based on these findings, the Effectiveness of Hypnobirthing in Reducing Low Back Pain Among Pregnant Women. It can be used as a novelty in further research. Conclusion: Researchers did not find research on the Effectiveness of Hypnobirthing in Reducing Low Back Pain Among Pregnant Women. Based on these findings, the Effectiveness of Hypnobirthing in Reducing Low Back Pain Among Pregnant Women can be used as a novelty in future research.